Observations on electrocardiogram and plasma catecholamines during dental procedures: the forgotten vagus. Issue 6039 (2nd October 1976) - Taggart, P; Hedworth-Whitty, R; Carruthers, M; Gordon, P D
Abstract : Emotional stress is conventionally considered to be associated with tachycardia and enhanced sympathetic activity. The electrocardiogram and plasma catecholamine and lipid concentrations were observed in 21 young healthy women undergoing dental procedures. Ten of these received premedication with the beta-blocking agent oxprenolol and 11 with a placebo, administered on a double-blind randomised basis. Mild tachycardia occurred in the placebo group a few minutes before and a few minutes after dentistry, but there was a reduction in heart rate immediately before and during the procedure. The pattern was similar in the group who received oxprenolol, though the heart rates at each stage were lower. Plasma adrenaline concentrations were much higher in the samples taken during the procedure than in those taken shortly before and after it. Plasma noradrenaline and lipid concentrations remained unchanged. A decrease in heart rate in the face of intense emotional arousal and an increased plasma adrenaline concentration suggest that the expectation or experience of pain may be associated with parasympathetic dominance despite greatly enhanced sympathetic activity.